Planetary boundary layer height by means of lidar and numerical simulations over New Delhi, India - K. Nakoudi; K. Nakoudi; K. Nakoudi; E. Giannakaki; E. Giannakaki; A. Dandou; M. Tombrou; M. Komppula (Atmospheric Measurement Techniques, 2019)
In this work, the height of the planetary boundary layer (PBLH) is investigated over Gwal Pahari (Gual Pahari), New Delhi, for almost a year. To this end, ground-based measurements from a multiwavelength Raman lidar were used. The modified wavelet covariance transform (WCT) method was utilized for PBLH retrievals. Results were compared to data from Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) and the Weather Research and Forecasting (WRF) model. In order to examine the difficulties of PBLH detection from lidar, we analyzed three cases of PBLH diurnal evolution under different meteorological and aerosol load conditions. In the presence of multiple aerosol layers, the employed algorithm exhibited high efficiency (r=0.9) in the attribution of PBLH, whereas weak aerosol gradients induced high variability in the PBLH. A sensitivity analysis corroborated the stability of the utilized methodology. The comparison with CALIPSO observations yielded satisfying results (r=0.8), with CALIPSO slightly overestimating the PBLH. Due to the relatively warmer and drier winter and, correspondingly, colder and rainier pre-monsoon season, the seasonal PBLH cycle during the measurement period was slightly weaker than the cycle expected from long-term climate records.